GEOCHRONOLOGY OF THE NABWAL HILLS: A RECORD OF EARLIEST MAGMATISM IN THE NORTHERN KENYAN RIFT VALLEY - McDOUGALL Ia.; Watkins R.T. (My University, 2006)
The Nabwal Hills, northeast of Lake Turkana, contain a record of magmatism associated with the initiation and early development of the East African Rift System in northernmost Kenya. The predominantly volcanic Asille Group, 1400 m thick, directly overlies metamorphic basement and comprises a sequence of basaltic lava flows with significant intervals of rhyolitic pyroclastic units, and minor intercalations of fluviatile sediments. The basement gneisses yield K-Ar cooling ages on biotite of 510 and 522 Ma, typically Pan-African. The 40Ar-39Ar ages on alkali feldspar crystals from the rhyolitic units are concordant and show that the Asille Group spans an interval from at least 34.3 to 15.8 Ma, continuing to at least as young as 13 Ma based on previous measurements. Vertebrate fossil sites, containing primate remains, at Irile and Nabwal are shown to be 17 ± 2 Ma old, Early Miocene, based upon K-Ar age measurements on immediately overlying basalts. Variably reliable whole rock K-Ar ages, determined on basalt samples from low in the sequence, indicate that volcanism commenced as early as 34.8 Ma ago. The overall geochronological results show that magmatism in the Nabwal Hills began about 35 Ma ago in Late Eocene times, interpreted as the time of initiation of crustal extension that led to the development of this segment of the East African Rift System. The Asille Group is tilted about 6° to the SSW. This tilting occurred later than 13 Ma ago, and prior to the eruption of the flat-lying Gombe Group basalts. These basalts may have begun erupting about 6 Ma ago in Late Miocene times, although much of this volcanism occurred between about 3.9 and 4.2 Ma ago in Pliocene times. It is suggested that the main rifting, which continues today, commenced in Late Miocene times, less than 13 Ma ago, and is partly reflected in the tilting of the Asille Group.
Keywords: BASALTS; IGNIMBRITES; GEOCHRONOLOGY; KENYA; TECTONICS; Кайнозой::Неоген::Плиоцен; Кайнозой::Неоген::Миоцен; Кайнозой::Палеоген::Эоцен; Cenozoic::Neogene::Pliocene; Cenozoic::Neogene::Miocene; Cenozoic::Paleogene::Eocene